Autosomal dominant cone-rod dystrophy with negative electroretinogram. - Fujii, N (1995)
AIMS--The negative electroretinogram (ERG) is observed in many hereditary retinal disorders. However, no reports have described a negative ERG in a family with autosomal dominant cone-rod dystrophy. A Japanese family with autosomal dominant cone-rod dystrophy with negative ERG is described. METHOD--Members of a Japanese family with autosomal dominant cone-rod dystrophy were examined and evaluated with Goldmann and Humphrey perimetry, bright flash ERG with an intense white stimulus, rod, cone, and flicker ERGs, and fluorescein angiography. Molecular analysis of the rhodopsin and peripherin/RDS genes in the patients was also performed. RESULTS--A 45-year-old Japanese man (proband) presented with decreased visual acuity. His fundi revealed bull's eye maculopathy and his single flash bright ERG showed a negative configuration. Negative ERG responses also were found in his father, who had macular degeneration, and one of the proband's three children who showed no fundus changes. No irregularities were found in their rhodopsin or peripherin/RDS genes. CONCLUSION--The condition of this family is believed to represent a previously undescribed autosomal dominant cone-rod dystrophy.